Giant Magnetoresistance of Mechanically Alloyed Fe7.5 Co22.5 Ag70 Mixed with Hard Magnetic Material - Chitnarong Sirisathitkul; John Gregg; Neil Cohen (Agriculture and Natural Resources, 2002)
Giant magnetoresistive Fe7.5Co22.5Ag70 was alloyed by ball milling for 60 hours. Subsequently, samarium-cobalt (5% by weight) was added to the alloy and the milling continued for another 15 minutes. The inclusion of hard magnetic SmCo5 was evidently not detriment to giant magnetoresistance (GMR). At room temperature, the bulk mechanical alloy exhibited coercivity of 500 Oe and 1.4 % GMR with modest anisotropic magnetoresistance. GMR increased linearly with decreasing temperature from 300 K to 143 K because the alloy’s resistance decreased at low temperature. Significant relaxation time of magnetic moments was observed in magnetoresistance curves as a lag of resistance change behind the field change.